The correlation between the level of 25-hydroxyvitamin D [25(OH)D] and residency of multiple sclerosis patients in Montenegro – higher levels only in men in the north of the country - Vujisic, Slavica M; Vodopic, Sanja; Idrizovic, Zilha; Radulovic, Ljiljana (Vojnosanitetski pregled, 2020)
Background/Aim. Multiple Sclerosis (MS) is a chronic neurological disease associated with low serum levels of 25-hydroxyvitamin D [25(OH)D]. The aim of this study was to determine the association between serum levels of 25(OH)D and the latitude as well as clinical MS severity and progression expressed by expanded disability status scale (EDSS) and multiple sclerosis severity score (MSSS). Methods. A total of 196 patients, from North and South of Montenegro, aged 18 to 65 years, with confirmed diagnosis of MS were recruited for the study. Serum samples were collected for 25(OH)D measurement. Control group consisted of 196 health controls, randomly selected from medical staff employed in health centers from three cities in North and Clinical Centre of Montenegro from the South. Results. The serum levels of 25(OH)D were significantly lower in MS patients compared to controls (p < 0.001). The serum levels of 25(OH)D were significantly different in regard to gender, with women showing lower levels. Although in the entire group of patients there was no statistical correlation between the levels of 25(OH)D and their residence, the significantly higher levels of 25(OH)D were detected in men from the North compared to women. The course of the disease had an impact on the 25(OH)D serum levels. 25(OH)D levels also significantly correlated with clinical parameters of both, disability (Spearman’s r = -0.23, p = 0.001) and progression (Spearman’s r = -0.25, p = 0.0004) of MS. Conclusion. Serum levels of 25(OH)D were associated with disability and progression in MS patients. Lower levels of 25(OH)D were detected in female patients from the North. The low level of 25(OH)D cannot be solely explained with unfavorable latitude and insufficient sun exposure, therefore further genetic analysis is needed.